plant taxa used as brooms in several southeast european and west asian countries - (:unkn) unknown (Croatian Natural History Museum, 2008)
The aim of this study is to determine the plants used as brooms by individuals and municipal authorities in some Southeast European (Bulgaria and Turkey) and West Asian (Azerbaijan, Saudi Arabia and Yemen) countries. The study was carried out from 1999 to 2005. At the end of the study, it was identified that 19 plant taxa belonging to 12 different families were used as brooms in the five countries. Among these species, Sorghum bicolor (broomcorn) was determined to be used extensively by municipal authorities for sweeping streets (Bulgaria) and by individuals for houses (Turkey and Azerbaijan). Erica sp. (tree heath) is commonly preferred by municipal authorities for sweeping streets in many areas of Turkey. We have established that the panicles and above ground parts of these plants are mostly used as brooms. Asteraceae is the largest family, represented by five species used as brooms. It is followed by Plumbaginaceae and by Poaceae with two species.
Keywords: Broom; Ethnobotany; Plant; Southeast Europe; Tradition; Western Asia